Tajdiid Ta'liim Al-Lughah Al'Arabiyah Min Naahiyatil 'Amaliyah - Rusdi Rusdi (Jurnal Alsinatuna, 2015)
The success of learning process including Arabic language learning is closely related to teachers’ competence. Good learning process is created when the teacher has good competence both in the theory of language and managing the class. Therefore, it is an obligatory for Arabic teachers to master language competence and language skills. Moreover, in this globalization era, it is necessary for Arabic teachers to involve technology in the teaching and learning process in order to create interesting and fun classroom activities